Notes on the State of Capital - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2010)
These notes are transcribed from a commentary on a paper by Sean Starrs, titled 'State and Capital: False Dichotomy But Still Inter-Related'. Both the paper and the commentary were presented as part of an integrated panel series on 'Capital as Power', held at the 36th Annual Conference of the Eastern Economic Association in Philadelphia, February 26-28, 2010. Sean Starrs claims that we need to discard our notion of the 'state of capital'. The gist of his argument is simple enough. Capitalist societies, he says, involve a myriad of power relations, many of them very important. These relationships, although often linked to the logic of capital, are distinct from that logic and therefore cannot be reduced to it. And since we are talking about separate social processes, we cannot encompass them all under the same rubric. His conclusion: the notion of a totalizing mode of power – which we call the state of capital – must be dispensed with. The notes attempt to clarify. They seek to explain, first, what we mean by a 'mode of power', and, second, why we use this concept in the first place. The sequence of our presentation is as follows. We begin by contrasting two spatial conceptions of the state. We then explain the notion of capitalization, which in our view represents the logic of the state of capital. And, finally, we flesh out the argument with a series of historical examples.
Keywords: 330; capital; capitalization; China; environment; power; public debt; state; war